Integration of clinical cases into a medical educational program with the aim of acquiring comprehensive practical skills on an example of fetal alcohol syndrome. - Paley, B.; O’Connor, M.J.; Baillie, S.J.; Guiton, G.; Stuber, M.L. (Морфологія / Morphologia / Morfologìâ, 2011)
In the article, on an example of a topic that deals with fetal alcohol syndrome, the relationship between the study of basic neuroscience and clinical practice is described. To this end, the Center for Disease Control and Prevention, together with the National Alcohol Fetopathy Organization, as well as the Los Angeles West Regional Center for Personnel Training on the Impact of Alcohol on Fruit, developed and proposed integrating materials related to Fetal Alcohol Syndrome, to the curriculum of the students of the first year of medical university. Results Quantitative and qualitative assessment of the results showed the effectiveness of studying materials, which affected the level of knowledge and mastery of practical skills, which concerned not only the actual alcoholic fetopathy, but also embryology, neurogenesis, developmental psychopathology and medical ethics. Conclusion. Creating comprehensive topics that combine basic theoretical knowledge with clinical knowledge and skills is an effective method for quality training of students from medical universities in the field of prevention and treatment of the most common health problems.